(untitled) (REMUNOM, 2026)
Food and Fandango are part of the caiçara culture and knowledge, as elements that intertwine and manifest themselves as a celebration at the end of a day of collective work, the mutirão. This text addresses the relationship between caiçara popular culture and food, and reflects on caiçara cuisine, identity, and the cultural revival of traditions. The justification for the theme comes from the problematization of the relationship between Fandango and the popular knowledge of caiçara cuisine and its presence today. This raises a question to be answered during this study: is it possible to maintain a cultural tradition such as caiçara cuisine today? The objective of this text is to understand how caiçara cuisine contributes to cultural strengthening, resistance, and preservation of caiçara identity. The study examines the transmission of culinary knowledge, the relationship between cuisine and cultural identity, and questions the importance of preserving and promoting the cultural heritage of caiçara communities. The methodology used in this research is qualitative, exploratory, and descriptive, through bibliographic, autobiographical, and documentary research, as well as interviews with the community. The results point to the appreciation of caiçara cuisine and the continuity of this knowledge, adapted to the present day. The results also show a change in the subsistence of the caiçara people, who began to use caiçara cuisine as a source of income, transforming their food into gastronomic tourism, thereby gourmetizing caiçara culture.